2021
DOI: 10.4028/www.scientific.net/kem.892.74
|View full text |Cite
|
Sign up to set email alerts
|

Failure Analysis of the Short Drive Shaft in a Screw Press Machine

Abstract: The screw press is a type of machine press used for extracting crude palm oil from the oil palm’s mesocarp, where its short driveshaft, a mechanical component for transmitting torque and rotation, is often found to be susceptible to failure. Since the initial damage to the short driveshafts in the shaft keyway area is associated with the frequent incidence of shaft failure, this research aimed to discover the root cause of this failure and how to prevent it using visual inspection and stress analysis methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Open belt, as shown in Figure 6, was considered because of its flexibility. Typically, the length of belt, power transmitted, angle of contact or lap, and load carried by the screw were designed according to Firdaus et al (2017) and Muhammad et al (2021) reported ineffective press (in terms of high oil loss and nut breakage), and shaft failure during testing of constant pitch screw press machine.…”
Section: Belt Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Open belt, as shown in Figure 6, was considered because of its flexibility. Typically, the length of belt, power transmitted, angle of contact or lap, and load carried by the screw were designed according to Firdaus et al (2017) and Muhammad et al (2021) reported ineffective press (in terms of high oil loss and nut breakage), and shaft failure during testing of constant pitch screw press machine.…”
Section: Belt Designmentioning
confidence: 99%
“…On the other hand, a screw press with uniform pitch shaft uses high speed/high power motor to effectively extract oil from oil-based seed materials, thus affecting cost (Olayanju et al, 2016). In the performance evaluation of some screw press, Firdaus et al (2017) and Muhammad et al (2021) reported ineffective press (in terms of high oil loss and nut breakage), and shaft failure, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of screw presses is evaluated for throughput capacity, feed rate, press cake oil content, oil expelling efficiency, percentage un-pressed grits output, percentage sludge output, and specific energy consumption [23]. The driveshaft of screw press is often found to be susceptible to failure, it is important to discover the root cause of this failure and the ways of its prevention [24]. The mechanical oil extraction using a commercial screw press was evaluated in the study [25].…”
Section: Introductionmentioning
confidence: 99%